Effectiveness of Fish Meal Substitution Using Maggot Meal in Floating Pellets on The Growth and Life Survival of Tilapia Fish (Oreochromis niloticus) - Sirait, Florentina Pauli; Afriani, Dwi Tika; Manullang, Helentina Mariance (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2024)
This research was conducted in February-March 2023, at the Dharmawangsa University Laboratory. The purpose of this study was to determine the effectiveness of fish meal substitution using maggot flour in floating pellets on growth, life expectancy of tilapia and FCR (Food Conversion Ratio). Tilapia is widely cultivated by the community so that it has economic value with high market demand. The high price of feed causes many farmers to suffer losses. To overcome the problem of losses, cultivators use maggot as a substitute for fish meal to be used as a local raw material which has the advantage of being relatively cheap, high protein and increasing the digestibility of fish. The research method used experimental methods with the treatment of artificial feeding with fish meal protein sources and maggot flour protein sources and analyzed using the T test. The results of absolute growth research on fish meal pellets were 3.5 and maggot flour pellets 3.6. This shows that maggot flour can be used as a local raw material in the manufacture of fish feed. The results of the survival rate of tilapia by giving fish meal pellets were 60% and giving maggot flour pellets was 55%. Fish meal pellets and giving maggot flour pellets show that they can support the basic needs of fish and can support fish life. The results of the study showed that the FCR value for fish meal pellets was 1.36 and for maggot flour pellets was 1.36.